2005
DOI: 10.1590/s1516-93322005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do teor de soro, açúcar e de frutooligossacarídeos sobre a população de bactérias lácticas probióticas em bebidas fermentadas

Abstract: Nos últimos anos tem havido muito interesse por produtos alimentícios de baixas calorias e probióticos. A incorporação de INTRODUÇÃOOs efeitos benéficos dos leites fermentados tiveram sua base científica no começo do século XX, com o microbiologista russo Eli Metchnikoff, que propôs uma teoria sobre o prolongamento da vida baseado no consumo diário de leites fermentados pelos povos dos Bálcãs (González, 1997). Ele acreditava que a atividade metabó-lica das bactérias ácido-láticas inibiria as bactérias intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 7 publications
(6 reference statements)
4
21
0
3
Order By: Relevance
“…No effect (p > 0.05) of inulin addition (WGI and SCI) on Lactococcus counts was observed for WG and SC formulations. During refrigerated storage, the Lactococcus population was between 10.88 and 13.47 log CFU.mL -1 , which is in agreement with the findings of Thamer and Penna (2005) (8.90 to 13.38 log CFU.mL -1 ), and it was higher than the that found by Wszolek et al (2001) (8.34 to 9.14 log CFU.mL -1 ) and Garrote, Abraham and De Antoni (1997) (9.78 log CFU.mL -1 ).…”
supporting
confidence: 90%
“…No effect (p > 0.05) of inulin addition (WGI and SCI) on Lactococcus counts was observed for WG and SC formulations. During refrigerated storage, the Lactococcus population was between 10.88 and 13.47 log CFU.mL -1 , which is in agreement with the findings of Thamer and Penna (2005) (8.90 to 13.38 log CFU.mL -1 ), and it was higher than the that found by Wszolek et al (2001) (8.34 to 9.14 log CFU.mL -1 ) and Garrote, Abraham and De Antoni (1997) (9.78 log CFU.mL -1 ).…”
supporting
confidence: 90%
“…Between the 22nd and 29th day of storage, all treatments presented counting below 10 4 CFU/mL, which is out of the standards established by the current legislation on identity and quality standards of fermented milk (BRASIL, 2007). According to Thamer and Penna (2005), a pH below the ideal interferes with the viability of probiotic colonies in the food, thus reducing the viable Lactobacillus cell counting. Shah (2000) reported that, in addition to the acidity produced during the storage period, the exchange of oxygen between packaging and the atmosphere influences lactic bacteria life, being the sensitivity to substances produced by yogurt bacteria and the lack of nutrient the factors responsible for the loss of viability of probiotic microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found probiotic populations of 10 7 CFU / mL across 28 days of refrigerated storage. Thamer and Penna (2005) evaluated 12 formulations of dairy beverages containing Bifidobacterium spp. And Lactobacillus acidophilus.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Different dairy product formulations can act positively or negatively on the multiplication of probiotic microorganisms (THAMER;PENNA, 2005). In the present study, the addition of the prebiotics oligofructose (PO) and inulin (PI) to dairy beverages did not affect the viability of L. paracasei, as significant differences (p> 0.05) were observed in these populations between formulations containing prebiotics (PI and PO) and the P formulation with L. paracasei only for all storage periods (Figure 2).…”
Section: Microbiological Analysesmentioning
confidence: 99%
See 1 more Smart Citation